Factors affecting Cyperus difformis seed germination and seedling emergence - Derakhshan,A. (2013)
Specific knowledge about the dormancy, germination, and emergence patterns of weed species aids the development of integrated management strategies. Laboratory studies were conducted to determine the effect of several environmental factors on seed germination and seedling emergence of Cyperus difformis. Germination of freshly harvested seeds was inhibited by darkness; however, when seeds were subsequently transferred to complete light they germinated readily. Our results showed that 2 wk of cold stratification overcome the light requirement for germination. Seeds of C. difformis were able to germinate over a broad range of temperatures (25/15, 30/20, 35/25, and 40/30 ºC day/night). The response of germination rate to temperature was described as a non-linear function. Based on model outputs, the base, the optimum and the ceiling temperatures were estimated as 14.81, 37.72 and 45 ºC, respectively. A temperature of 120 ºC for a 5 min was required to inhibit 50% of maximum germination. The osmotic potential and salinity required for 50% inhibition of maximum germination were -0.47 MPa and 135.57 mM, respectively. High percentage of seed germination (89%) was observed at pH=6 and decreased to 12% at alkaline medium (pH 9) pH. Seeds sown on the soil surface gave the greatest percentage of seedling emergence, and no seedlings emerged from seeds buried in soil at depths of 1 cm.